2016
DOI: 10.1038/srep37901
|View full text |Cite
|
Sign up to set email alerts
|

Novel Ti-Ta-Hf-Zr alloys with promising mechanical properties for prospective stent applications

Abstract: Titanium alloys are receiving increasing research interest for the development of metallic stent materials due to their excellent biocompatibility, corrosion resistance, non-magnetism and radiopacity. In this study, a new series of Ti-Ta-Hf-Zr (TTHZ) alloys including Ti-37Ta-26Hf-13Zr, Ti-40Ta-22Hf-11.7Zr and Ti-45Ta-18.4Hf-10Zr (wt.%) were designed using the d-electron theory combined with electron to atom ratio (e/a) and molybdenum equivalence (Moeq) approaches. The microstructure of the TTHZ alloys were inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 53 publications
1
22
0
2
Order By: Relevance
“…At present, laser-cutting technology has been used in the manufacture of tubular stents. Our previous study 9 demonstrated that the as-cast Ti-40Ta-22Hf-11.7Zr (TTHZ) alloy exhibited high strength (compressive yield strength, tensile strength, and tensile yield strength), high elastic admissible strain (1.58%, compared to 0.21-0.31% for the Co-Cr alloy), high microhardness, and excellent cytocompatibility; such characteristics are of great signicance for the alloy's ability to be used as selfexpanding stent material. The present study explores further improvement in its mechanical properties through the process of solution treatment (ST) and aging, and examines the corrosion resistance of the alloy, which is one of the most important parameters in assessing metallic biomaterials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, laser-cutting technology has been used in the manufacture of tubular stents. Our previous study 9 demonstrated that the as-cast Ti-40Ta-22Hf-11.7Zr (TTHZ) alloy exhibited high strength (compressive yield strength, tensile strength, and tensile yield strength), high elastic admissible strain (1.58%, compared to 0.21-0.31% for the Co-Cr alloy), high microhardness, and excellent cytocompatibility; such characteristics are of great signicance for the alloy's ability to be used as selfexpanding stent material. The present study explores further improvement in its mechanical properties through the process of solution treatment (ST) and aging, and examines the corrosion resistance of the alloy, which is one of the most important parameters in assessing metallic biomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the molybdenum equivalence (Mo eq. ) 32 of the TTHZ alloy is 8.8, 9 and the martensite phases a and a 00 did not appear aer WQ but did so aer aging, followed by the reconstruction of lattices which drove the transition of the original body-centered cubic (bbc) b phase to the orthorhombic martensite a 00 phase. The martensite a 00 phase exhibited unstable thermodynamic properties and phase transformations took place during the aging process.…”
mentioning
confidence: 99%
“…This may be attributed to the present low aging temperature and short aging time, which limits the diffusion of the alloying elements and, consequently, the size and distribution of the precipitates. To the best of our knowledge this level of modulus is much lower than those of the currently available biomedical Ti alloys 1,6 .…”
mentioning
confidence: 72%
“…As a result, the conventional annealing treatments normally cause an undesirable raise in the elastic modulus of the alloy, making it difficult to simultaneously reach low elastic modulus and high yield strength 1 . Therefore, several studies have been currently carried out with the purpose of finding a method able to strengthen metastable β-Ti alloys without substantially modifying their elastic modulus [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Biomédicas: Algumas propriedades relevantes dos VMMs para a medicina foram tratadas na seção anterior. Assim, a biocompatibilidade e resistência à biocorrosão motivam aplicações de VMMs em dispositivos metálicos regularmente implantados em procedimentos médico-cirúrgicos, tais como próteses ortopédicas e "stents" cardiovasculares [15,41]. No caso de "stents", já existe inclusive patente [42].…”
Section: Aplicações Dos Vidros Metálicos Maciçosunclassified